Shading by Trees and Fractional Snow Cover Control the Subcanopy Radiation Budget. Issue 6 (21st March 2019) - Malle, Johanna; Rutter, Nick; Mazzotti, Giulia; Jonas, Tobias
Abstract: Radiative processes are substantially altered by the presence of forest canopies, further affecting snow energetics during wintertime. In situ measurements of subcanopy radiation can help improve process‐scale understanding of these complex interactions, which are needed to further constrain and improve land surface models. In this study, a custom‐made cable car was used to measure incoming and outgoing, shortwave and longwave radiation below an evergreen forest stand. Hemispherical photographs taken concurrently from the cable car measured view fractions of shaded snow, sunlit snow, and bare ground. With this setup it was possible to quantify diurnal and seasonal radiation patterns together with their potential drivers at high spatiotemporal resolution. Measurements were performed between January and May 2018, along a 48‐m transect in a discontinuous needleleaf forest in the Swiss Alps. Analysis of diurnal radiation patterns revealed a strong linear relationship ( R  = 0.94) between outgoing shortwave radiation and sunlit snow‐view fraction, highlighting shading as the main control on the subcanopy shortwave radiation budget. Measurements of outgoing longwave radiation were strongly controlled by the snow cover extent, with locations of diminished snow cover showing an increase in outgoing longwave radiation of up to 60 W/m 2 . The subcanopy radiation budget was shown to be dominated by shortwave radiation when surrounding canopy structure and the position of the sun allowed for direct insolation of the forest floor, but longwave radiation was the dominating component in the absence of direct insolation. Key Points: Radiation measurements were taken concurrently with downlooking hemispherical imagery to determine the spatial extent of shaded/sunlit snow Shading by trees and fractional snow cover were shown to exert key controls on the subcanopy radiation budget Subcanopy radiation measurements revealed a linear relationship between outgoing shortwave radiation and the view fraction of sunlit snow